The Ultimate French Review and Practice - Stillman, David M.; Gordon, Ronni L. (New York : McGraw-Hill, 2016)
Presents a guide to French grammar for intermediate and advanced English speakers.
Includes index.
Keywords: French language -- Grammar; French language -- Self-instruction.; French language -- Sound recordings for English speakers